Conservation Strategies for the Mangroves of Andaman & Nicobar Islands - Maria Dominic Savio, M.; Singh, Mudit Kumar (Indian Forester, 2006)
Sustainable use is a current theme of prime importance for better utilization of natural resources, through rationale and responsible multiple use management practices. Mangroves, a fragile ecosystem is one among the most productive and biodiversity rich wetlands on earth. Growing in the intertidal areas and estuary mouths, the mangroves provide critical habitat for a diverse marine and terrestrial flora and fauna. Andaman and Nicobar Islands, which accounts for nearly 9.5% of the total mangrove vegetation in India is the least disturbed and the best preserved in India. Due to its remoteness and low anthropogenic pressure the virgin mangrove forests are still prevalent Andaman and Nicobar Islands. Rural populations residing in the coastal areas of these Islands depend on them for day to day livelihood needs. One to three members from about 46% of the families residing in mangrove bearing villages are engaged in fishing. The ever increasing human population in the form of settlers mainly over the past four decades is posing a serious threat to the Andaman forests especially to the mangrove ecosystem. This paper reviews the mangrove resources, economic dependence, past and present management strategies and also discusses the potential for future conservation strategies in terms of people participatory programs, ecotourism and social forestry programs in Andamans.